Jackie after O : one remarkable year when Jacqueline Kennedy Onassis defied expectations and rediscovered her dreams /: one remarkable year when Jacqueline Kennedy Onassis defied expectations and rediscovered her dreams. (©2012) - Unknown
No abstract available